Motivasi Belajar Perspektif Al-Syarqawi dan Relevansinya terhadap Minat Belajar Peserta Didik - Masna Nurfadilah; Achmad Muhlis (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to explore Al-Syarqawi’s concept of learning motivation and its relevance to the development of students’ interest in learning within the framework of modern Islamic education. The research adopts a qualitative approach with a library research method and applies content analysis to Al-Ta’allum: Al-Nadhariyat wa Al-Tatbiqiyyah and other relevant references. The results show that Al-Syarqawi places motivation as a fundamental condition that determines the continuity and success of the learning process. Motivation, both intrinsic and extrinsic, covers spiritual, psychological, social, and biological dimensions that guide students toward meaningful learning experiences. Al-Syarqawi emphasizes that spiritual motivation should be integrated into the educational process to create balance between intellectual development and moral-spiritual growth. His thought remains relevant to holistic and character-based education, especially in the context of the Merdeka Curriculum, which promotes student independence, creativity, and moral responsibility. Thus, this study contributes to enriching Islamic educational thought by providing an integrative perspective that harmonizes spiritual, psychological, and pedagogical values to enhance students’ motivation and learning engagement.